How Can the HIV Counselling Programme in the Una District, Himachal Pradesh State, Northern India, Be Made More Effective? An Appreciative Inquiry by Frontline Counselling Staff and High-Risk Clients - Nair, Balakrishnan Sukumaran (Auckland University of Technology, 2023)
Human Immunodeficiency Virus (HIV) counselling of high-risk groups (HRGs) is an under-researched area in India. HRGs include female sex workers (FSWs), men who have sex with men (MSM), injecting drug users (IDUs), Hijra/transgender people (HTG), single migrant men (SMM), and long-distance truckers (LDTs) have a higher HIV prevalence compared to adult HIV prevalence in India. HRGs are often at risk because of a number of social, organisational, and management factors. These barriers affect how HRGs access and engage with the Indian HIV counselling programme. The HIV counselling programme is the key point of access or entry to HIV diagnosis and treatment for HRGs. HRGs are the key clients for the programme. Internationally, studies indicate that it is an effective measure to ensure regular HIV testing, reduce the risk of transmission, and improve the health and well-being of HRGs. This study investigated the research question “How can the HIV counselling programme delivered in Una district, Himachal Pradesh state, Northern India, be made more effective?” Given that they are key clients this study adopts the perspective of HRGs and also the perspectives of the counsellors associated with the HIV counselling programme. The first sub-question explored current knowledge about the evolution of the Indian HIV programme and how that has shaped effectiveness today. As the empirical part of the study, research sub-questions two and three focused on engagement with the co-researchers as a means of exploring the effectiveness of the HIV counselling programme through their lens. The study adopted a participatory research methodology, specifically appreciative inquiry (AI), for eliciting the perspectives of HRGs and frontline counselling workers (FCS), acknowledging their critical roles as clients and workers. AI further became the means of identifying strengths-based solutions to improve a public health programme (PHP) and bringing of positive change within organisational settings. The AI phases of the research process—called the 4D phases—were discovery, dream, design, and delivery. HRGs and FCS, who conducted this AI through focus group discussions (FGDs), have been referred to in the study as ‘co-researchers’ (CRs). Like other participatory research methods, AI follows a strengths-based approach. However, it is distinguished by its capability in providing a space for the voices within an organisation, in this case that of FCS and HRG clients; and to address an organisational issue, that of HIV counselling programme effectiveness. The findings are presented in three chapters. The first findings chapter represents the discovery of the organisational, management factors that affect the implementation and success of HIV testing and counselling programmes in Una. The issues raised by CRs in relation to the resources and infrastructure required, and policies and procedures necessary for the effective operation of the programme are examined. The next chapter of discoveries is from a sociocultural lens focusing on the neglected cultural and social factors that affect the accessibility and uptake of counselling services. It revealed that the programme ignored the belief systems of HRGs and often overlooked the personal and social implications of being associated with an incurable and stigmatised illness which often leads to denial of a HRG from a positive diagnosis or even defiance towards accessing HIV counselling services. The final findings chapter revisits the 4Ds as a guide to developing an effective HIV counselling programme, concluding with a discussion on how it would be implemented in a real setting. The study findings have implications for transformed approaches to addressing the challenges faced by HRGs when accessing the HIV counselling programme in Una. Policy and programme recommendations include the need for a more contextualised and social determinants-based approach; promotion of indigenous ways of counselling; and inclusion of CRs’ perspectives in planning, development, and operations. The study contributes to the growing body of literature that uses AI as a methodology and examines the issues of people at risk of, or living with, HIV/AIDS. It paves a valuable path for a culture of transformation, creating an environment for positive change and suggesting a wellbeing centred model for Indian HIV counselling programme.